Emmanuel Mounier’s idea of personalizm - Apiecionek, Michał (Filozofia Chrześcijańska, 2016)
The term personalism and the problem of the mystery of person has long occupied a prominent place in the study of philosophy. One of the most famous proponents of the idea of personalism is a French philosopher Emmanuel Mounier. His broad philosophical education has become an inspiration to attempt to create a philosophy defending the value of man as a person. Starting from Christian thought he tried, using multiple and sometimes conflicting philosophies, to build a personalistic system, the center of which is a person. It was reflected in his selection of collaborators publishing in his journal “Esprit”, where philosophers of various denominations wrote, but the source of their common interests was a person. Personalism, according to Mounier, is a philosophy that comprehensively solves the problem of the person, on spiritual and material levels, and is a counterweight to the individualistic and collectivist tendencies. Trying to explain the mystery of the person, he does not give a precise definition, because the person is not the object, which can be simply defined. Personalism developed by Mounier is not a closed system, but just like the human being it is in the process of continuous becoming. It is a response to the crisis of man searching his identity as a person in the world.